The Study of Household Waste Generation to Support Jababeka Smart Township Initiative - Yunita Ismail Masjud; Felix Goenadhi; Ihsan Hadiansah (President University, 2022)
Abstract. The problem of household waste faced in industrial areas is becoming increasingly urgent, considering that industrial areas are areas that are growing very rapidly. Jababeka Smart Township initiative is one of the efforts to provide services to the community, to improve sustainable living. In waste management, it takes the amount of waste generated to be managed, so that the measurement of household waste generation is the first step needed. Objectives: The objectives of this research are to know the waste generation at Jababeka residential, to know the waste generation of Mekarmukti village, and to analyze the waste generation in Jababeka area. Method and results: The method of measuring household waste generation used follows SNI 19-3964-1994. The population used in this study were Mekarmukti villagers, both living in housing and outside housing. Purposive sampling method used in find the sample, method of data collection was observation, and descriptive statistics used for data analysis. The result found that the average waste generation from people at Jababeka residential is 0.33 kg/day/person, and out of residential is 0.37 kg/day/person. In Mekarmukti village, center of waste recycle could used to manage the household waste Based on this average waste the potential technology could implemented the solid waste management. Conclusion: The average waste generation in Jababeka residential is 0.33 kg/day/person and outside of residential is 0.37 kg/day/person, and this amount still less than the average waste produced per person per day in Indonesia.